Comparative Study of a Three Phase Cascaded H-Bridge Multilevel Inverter for Harmonic Reduction - Rosli Omar; Mohammed Rasheed; Marizan Sulaiman; M. R Tamijis (Institute of Advanced Engineering and Science, 2015)
The aim of this research project is to analyze and design of energy storages in electrical distribution system. In this paper presents a comparative study between sinusoidal pulse width modulation (SPWM) and space vector pulse width modulation (SVPWM) technique, based on generate signal five level of cascaded H-bridge for reduction harmonics in the multilevel inverter output. A multilevel inverter is a preferred choice for most medium-voltage and high-power applications, as well as cascaded H-bridge (CHB) five-level inverters due to its advantages such as low cost, light weight and compact size. It is suitable particularly for use in a cascaded H-bridge multilevel inverter due to reduced total harmonic distortion (THD). Harmonic content in three phase multilevel inverter can be investigated by generating (SPWM) and (SVPWM) algorithm signal based on a five-level (CHB). The proposed system is designed using MATLAB/SIMULINK consists of cascaded H-bridge (CHB) multilevel inverter. DOI: http://dx.doi.org/10.11591/telkomnika.v14i3.7949